A method for estimating the diffuse attenuation coefficient (KdPAR) from paired temperature sensors. (11th February 2015) - Read, Jordan S.; Rose, Kevin C.; Winslow, Luke A.; Read, Emily K.
Abstract: A new method for estimating the diffuse attenuation coefficient for photosynthetically active radiation ( K d PAR ) from paired temperature sensors was derived. We show that during cases where the attenuation of penetrating shortwave solar radiation is the dominant source of temperature changes, time series measurements of water temperatures at multiple depths ( z 1 and z 2 ) are related to one another by a linear scaling factor ( α ). K d PAR can then be estimated by the simple equation K d PAR = ln( α )/( z 2 − z 1 ). A suggested workflow is presented that outlines procedures for calculating K d PAR according to this paired temperature sensor (PTS) method. This method is best suited for conditions when radiative temperature gains are large relative to physical noise. These conditions occur frequently on water bodies with low wind and/or high K d PAR s but can be used for other types of lakes during time periods of low wind and/or where spatially redundant measurements of temperatures are available. The optimal vertical placement of temperature sensors according to a priori knowledge of K d PAR is also described. This information can be used to inform the design of future sensor deployments using the PTS method or for campaigns where characterizing sub‐daily changes in temperatures is important. The PTS method provides a novel method to characterize light attenuation in aquatic ecosystems without expensive radiometric equipment or the user subjectivity inherent in Secchi depth measurements. This method also can enable the estimation of K d PAR at higher frequencies than many manual monitoring programs allow.